2013
DOI: 10.1002/apj.1767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesh grid and turbulence models on heat transfer coefficient in a convergent–divergent nozzle

Abstract: The results of computational fluid dynamics simulation for convective heat transfer of turbulent flow in a cooled convergent-divergent nozzle are reported. The importance of the heat transfer coefficient is to find the most suitable metals for the nozzle wall as well as its application for producing nano-particles. ANSYS-ICEM and ANSYS-CFX 13.0 are used to mesh and simulate fluid flow in the nozzle, respectively. Effects of grid resolution and different turbulence models on the heat transfer coefficient are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Ronier 4 reservoir is divided into three single layers. After the layering of the single layer, the planar grid scaling in Block Ronier 4 is performed (Witt et al 2007;Zhalehrajabi et al 2014). The longitudinal grid scaling is divided as 0.3 m according to the minimum single sand body thickness of various sedimentary units (Ishak et al 2018;Khan et al 2001).…”
Section: Computational Methodologymentioning
confidence: 99%
“…Ronier 4 reservoir is divided into three single layers. After the layering of the single layer, the planar grid scaling in Block Ronier 4 is performed (Witt et al 2007;Zhalehrajabi et al 2014). The longitudinal grid scaling is divided as 0.3 m according to the minimum single sand body thickness of various sedimentary units (Ishak et al 2018;Khan et al 2001).…”
Section: Computational Methodologymentioning
confidence: 99%
“…A series of verification 26 tests were performed before proceeding for validations as in literature. 27,28 The ultimate setting is shown in Table 1.…”
Section: Computational Modelsmentioning
confidence: 99%
“…They also reported that the placement of the first cell near the wall strongly affects heat transfer prediction. A similar study by Zhalehrajabi 12 compared the effect of a number of grids and a turbulence model. They reported that heat flux estimation is grid sensitive, and results obtained using the k-ε turbulence model 13 are close to the experimental data than the k-ω SST [14][15] turbulence model.…”
Section: Introductionmentioning
confidence: 99%